Dve novi vrsti karabidov v favni Slovenije (Coleoptera: Carabidae) - Kapla, Andrej (Acta entomologica slovenica (Ljubljana), 2002)
Zuphium olens (Rossi, 1790) and Tachys fulvicollis Dejean, 1831 were found in Škocjanski Zatok near Koper. Both findings are first records of the species in Slovenia.
Keywords: Carabidae; Coleoptera; hrošči; Slovenia; Slovenija